Small-vessel-disease-induced white matter damage in occipital lobe epilepsy - Kim, Jinseung; Lee, Dong Ah; Lee, Ho-Joon; Park, Kang Min (Frontiers in Neurology, 2025)
BackgroundPeak width of skeletonized mean diffusivity (PSMD) is a novel marker of small vessel disease. This study aimed to investigate the presence of small vessel disease in patients with occipital lobe epilepsy (OLE) using PSMD.MethodsWe enrolled 27 patients newly diagnosed with OLE and included 29 healthy controls. The age and sex of the patients and controls were comparable. Diffusion tensor imaging (DTI) was performed using a 3 T MRI scanner. We measured the PSMD based on DTI in several steps, including preprocessing, skeletonization, application of a custom mask, and histogram analysis, using the FSL program. We compared PSMD between patients with OLE and healthy controls. Additionally, we performed a correlation analysis between PSMD and clinical factors in patients with OLE.ResultsOur findings revealed that the patients with OLE exhibited higher PSMD compared to healthy controls (2.459 vs. 2.079 × 10−4 mm2/s, p < 0.001). In addition, PSMD positively correlated with age (r = 0.412, p = 0.032). However, the PSMD of the patients with OLE was not associated with other clinical factors such as age at seizure onset and duration of epilepsy.ConclusionWe demonstrated that patients with OLE had a higher PSMD than healthy controls, indicating evidence of small vessel disease in patients with OLE. This finding also highlights the potential of PSMD as a marker for detecting small vessel diseases in epileptic disorders.